Compounded energy gains in collocated wind plants: Energy balance quantification and wake morphology description. (May 2020) - Kadum, Hawwa; Cal, Raúl Bayoán; Quigley, Mike; Cortina, Gerard; Calaf, Marc
Abstract: Large eddy simulations are used to investigate mechanisms to enhance power harvesting in wind farms. Specifically, the potential combination of vertical axis wind turbines (VAWT) with traditional horizontal axis wind turbines (HAWT) are studied to alter wake recovery, wake interaction, and thus increase power harvesting per unit area. For this purpose, three arrangements are studied: 1.) a standard wind plant with only horizontal axis wind turbines, 2.) an aligned collocated wind plant, and 3.) a staggered collocated wind plant. In the collocated wind plants, clusters of three vertical axis wind turbines are introduced to the standard wind farm and placed either in alignment to the horizontal axis wind turbines, or staggered between the rows. A control volume analysis is employed to examine the energy balance and relevant terms for the various characteristic compounded wakes. The results show that collocating HAWTs with VAWTs can increase or decrease power harvested per unit area depending on the collocation arrangement. VAWTs cause an increase in streamwise velocity that can be utilized to speed the inflow interacting with the HAWT rotor. In this study, placing VAWTs aligned to HAWTs and upstream to them resulted in a 3.5% increase in the power produced by the wind plant. Whereas, the staggered arrangement resulted in a 2.6% decrease. The aligned case also produces a merged wake that is similar in structure to a wake produced by a traditional horizontal axis wind turbine with heightened near surface Reynolds shear stress. The staggered configuration, on the other hand, behaves as two interacting wakes generating a more confined and intensified skewed wake. These findings show the influence of collocating VAWTs in HAWT plants, and suggest the possibility of optimizing the clusters arrangements in future investigations for higher power production density. Highlights: Vertical axis wind turbines are collocated with horizontal axis wind turbines. Collocation arrangement can increase or decrease power production. Collocated plants display enhanced mean kinetic energy transport. The added vertical axis wind turbine lead to sudden increase in streamwise velocity. Placing the VAWTs upstream and close to the HAWTs increases harvested power.